EARTHQUAKE FOCAL DEPTHS AND CRUSTAL STRENGTH IN THE BAIKAL RIFT - Radziminovich N.A.; Balyshev S.O.; Golubev V.A. (My University, 2003)
Earthquakes are an important source of knowledge on mode of deformation and strength of rocks. According to the available hypocenter locations and recent relocations, most of seismicity in the Baikal rift is confined to the upper 26-27 km of the crust. The base of seismogenic crust corresponds to transition from brittle failure to plastic flow. The 0-27 km depth range of brittle failure in rifts is consistent with mostly mafic crust, high pore pressure, and an "intermediate" geotherm. Crustal strength was estimated within the limits of a two-layer model assuming predominant frictional sliding in the upper crust and dislocation creep in the lower crust. The inferred depth of brittle-ductile transition for granites and diorites corresponds to the top of the crustal waveguide in the Baikal rift. However, low strength does not preclude nucleation of earthquakes in this layer. The brittle-ductile transition in the lower crust is at 21 km for diabase and 24 km for mafic granulite. The latter value approaches the lower depth limit of 90% hypocenters.
Keywords: Baikal rift; focal depths; crustal strength; brittle-ductile transition